Ghana: Accelerating neglected tropical disease control in a setting of economic development - Hotez, Peter J.; Biritwum, Nana-Kwadwo; Fenwick, Alan; Molyneux, David H.; Sachs, Jeffrey D. (PLoS neglected tropical diseases, 2019)
According to the GBD 2017, schistosomiasis is the second most prevalent human helminth infection (following hookworm infection) in Ghana, affecting almost one million people [9]. [...]among the arbovirus infections, the incidence of dengue in Ghana and elsewhere in West Africa is believed to have risen precipitously. According to WHO, Ghana is one of 14 countries considered at high risk of yellow fever outbreaks, although it is not currently one of the four West African nations considered as a “complex emergency situation” [50]. The concerns about albendazole resistance and reduced ivermectin efficacy will also need to be addressed, with consideration of developing improved biotechnologies for some of the NTDs [51]. [...]we have seen how dengue and yellow fever can persist even in middle-income countries, so that for these diseases as well new technologies will need to be developed and implemented.